Quality of service guarantee mechanism for enterprise video conference - Jian-feng DENG; Ling ZHANG; Jie ZHOU (Tongxin xuebao)
The QoS problem under the controlled enterprise network environment was addressed,and a novel QoS management mechanism for video conference at the enterprise level was proposed.This novel mechanism analyses the conference organization mode and transferring mode,and transforms the guarantee of video conference to the guarantee of a flow group with temporal information.This mechanism provides the bandwidth reservation through the management of network priority bandwidth.It authenticates labels and shapes the data flow at the edge of the network,and uses DiffServ to priority forward the media flow in the core network,and therefore guarantees the reservation of bandwidth for authorized users.Experimental results and analysis show that the proposed mechanism can provide the necessary bandwidth for the media flow when network congestion happens,and then can efficiently and effectively guarantee QoS for enterprise video conference.